TECHNOLOGY FOR IRON AND MANGANESE ION REMOVAL FROM GROUNDWATER: A REVIEW - Zevi, Yuniati; Septiyani, Elda (MATTER: International Journal of Science and Technology, 2020)
High concentrations of iron and manganese often cause issues. Based on grab sampling results in West Java, the average value of Fe concentration in groundwater is 0.97 mg/l and 0.64 mg/l for Mn. The results exceeded quality standard limit of 0.3 mg/l for iron and 0.1 mg/l for manganese. From these conditions, technology to remove iron and manganese is needed. One of the process to remove iron and manganese is to adsorb the two compounds by filtration method. The filtration method utilized mordenite minerals contained in Sukabumi Green Natural Stone. This study had two types of adsorbents which were activated and natural. Besides, the batch process in this experiment offers a result that activated and natural mordenite were able in diminishing the concentration of Fe and Mn from groundwater. Generally, batch experiment processes rely on the initial concentration and detention time during the adsorption, the process then carried out using continuous experiment. The continuous experiment process indicates clogging, so that the efficiency of removal obtained decrease with the usage period of the adsorbent. Furthermore, regeneration is needed to make the lifetime of mineral be longer and can be reused. The regeneration method utilized chemical and biological regeneration.